Analisis Pemilihan Elemen Water Sensitive Urban Design (WSUD) Kawasan Pinggir Sungai Kecamatan Rajabasa, Bandar Lampung - Winata, Lestari P; Pangkerego, Gabriel Efod Virant (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Rajabasa District in Bandar Lampung City is a strategically located area undergoing rapid development, primarily characterized by residential, educational, and transportation functions. However, unbalanced urbanization and inadequate environmental management have increased its vulnerability to flooding. In the past two years, floods have occurred due to river overflow during heavy rainfall, insufficient drainage infrastructure, and limited green open spaces for water absorption. These conditions underscore the urgency of adopting flood-adaptive planning strategies. This study investigates the potential application of the Water Sensitive Urban Design (WSUD) concept along the riverbanks in Rajabasa to enhance urban flood resilience. A mixed-method approach was employed, combining spatial analysis using GIS and field observations to assess existing conditions and identify priority areas for WSUD implementation, along with qualitative analysis of relevant literature and spatial planning documents. Findings reveal that the riverbank area is predominantly occupied by housing with low elevation, increasing the risk of water accumulation. To improve infiltration capacity, priority WSUD elements include rainwater storage tanks, raingardens, street trees/tree pits, swales (bioretention), permeable paving, and riparian buffers. Implementing these elements is expected to provide a foundation for flood-resilient urban planning and contribute to sustainable urban development. Keywords: flood; riverside area; WSUD